A contribution to the knowledge of myxomycetes diversity in volcanic islands. (3rd July 2016) - Compagno, R.; Gargano, M. L.; La Rosa, A.; Venturella, G.
Abstract : A list of myxomycetes collected in Pantelleria, a volcanic island located 110 km southwest of the island of Sicily (Italy), is presented with data on distribution. Forty-nine taxa were identified, 38 of which are new for Sicily. The myxomycete diversity of Pantelleria was also compared with that of other volcanic islands located in the Atlantic and Pacific oceans.